DEVELOPMENT OF PHYSICS LEARNING WEB BLOG BASED ON CONTEXTUAL TEACHING LEARNING (CTL) - Tanti Tanti; Nana Afriani; Maison Maison (Journal of Teaching and Learning Physics, 2023)
This study aims to construct and validate and analyze the effectiveness of a physics learning blog based on contextual teaching and learning. The method used in developing a physics learning blog is the ADDIE model. The physics learning blog was validated by material experts, media experts, and one physics teacher as a practitioner. The validation and practicality tests show that the module developed is valid and practical to use as a medium to increase students' learning motivation. The effectiveness test results using a one-class pre-test and post-test design showed increased student motivation before and after using a web blog. The learning web blog generated from this development research can be used as one of the teaching components specifically aimed at increasing students' learning motivation.